DAYA TERIMA NUGGET IKAN LELE YANG MEMANFAATKAN TEPUNG KACANG MERAH DAN KANDUNGAN GIZINYA - Jenny Feby Andriani Tarigan; Evawany Y Aritonang; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Technology of flouring is applied to the red bean into red bean flour in order to maintain its storability. Catfish is freshwater commodity with a good production but less utilized into various product. The combination of red bean flour and catfish can be processed into nuggets which could attract more people especially children. The purpose of this research is to find the acceptability of catfish nugget with red bean flour based on organoleptic analysis criterias including color, aroma, texture and flavor measured by the hedonic scale as well as to identify the level of nutrient contents of protein, fat, water, ash and carbohydrates. This is an experimental research, which consists of two factor, those are red bean flour and catfish using 3 different treatment. Each treatment using comparisons of red bean flour and catfish in amount 35% : 65%, 25% : 75% and 15% : 85% symbolized by A1, A2, A3. Panelists in this research are students of Elementary School 060929 Medan Johor of class VI A comprised 30 students. The result showed that the organoleptic test result of the nugget with red bean flour in treatment III (A3) that is most preffered by panelists, in terms of color, texture and flavor. Whereas for aroma criteria, nugget with red bean flour in treatment I (A1) is the most preffered by panelists. Based on the results of nutrient contents, nugget with the highest protein and water contents is contained in treatment A1 with each amount are 16,4474% and 36,457%, whereas the highest fat, ash and carbohydrate contents contained in treatment A3 with each amount are 29,7941%, 4,0877%, and 19,1318%. It is necessary to process more other ways catfish nugget with red bean flour to improve the acceptability as well as its quality in order to attract the consumer. Keywords: Red bean, Catfish, Nugget, Nutrient content